Identity Formation and Political Assertion among the Deoris - Deori, Bhupen (International Research Journal of Management, IT & Social Sciences, 2015)
Sub-regionalism or communalism, as we all know is a sentiment of similarity, amongst the people belonging to the same group. It means a sense of common consciousness or peoples under the same political organization. We know that there are different responsible causes for the resurgence amongst the tribal groups of North-East India and they have different natures, for example; aspiration for separate identity, aspiration for establishing an autonomous council, development council, creation of a new state and many more. Assam is a  part  of  the North-Eastern  region  of   India, a  district inhabited by  aboriginal  tribal  communities   in  this  state,  viz;  the  Bodos ,  Karbis,  Dimasas,  Mishings,  Deoris,  Rabhas,  Sonowal  Kacharis etc.  They  are distinguished  from  each-other  societies  by  certain  modes , behavior, character  such  as  dress code,  food habits ,socio-cultural  rituals  and  religious  belief. The Deoris  are  one  of  the  major  ethnic  plain  tribe  of  Assam. They  have  their  own  language  to  converse  amongst  themselves,  own religious  beliefs,  living  styles etc. Their present population is approximately two Lakhs According to census report of Deori autonomous council (DAC) . The Deories are settled mostly in the Districts of Lakhimpur, Dhemaji, Sibsagar, Dibrugarh, Jorhat, Sonitpur and Tinsukia of Assam and some villages are also situated in the Districts of Changlang, Lohit and Tirap of Arunachal Pradesh. The Deori Autonomous Council (DAC), a political organization of Deoris, established in 2005, to fulfill their socio-economic development. The aspiration of the Deori people for a separate identity is not a new concept. It has some longest historic stages.   It was seen that the struggle for a separate identity was began during the time of eighty decade, under the banner of the   All Assam Deori Student Union (AADSU), which formed in 1959. In this present article, we attempt to focus the aspiration of the Deori peoples and their struggle for a separate identity.